HUBUNGAN ANTARA STATUS GIZI DAN KEBIASAAN BEROLAHRAGA DENGAN TINGKAT KEBUGARAN JASMANI (STUDI PADA SISWA KELAS XI SMA NEGERI 4 SIDOARJO) - RAFSANJANI, RIZKI (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Nutrient status is a state of the body as a result of food consumption and utilization of nutrients in the form of specific variables that can be measured by certain methods. Nutrient status is low or normal will have an impact on the level of physical fitness. In addition to nutrient status, the sport habit can also affect the level of physical fitness. Sport habit is not excessive will result in above average, and by practicing sports activities will result in physical fitness level higher. So the influence on physical fitness has a greater percentage. The purpose of this study was to determine the correlation of nutrient status and sport habits with physical fitness level of class XI SMA Negeri 4 Sidoarjo and to determine the contribution of nutrient status and sport habits to the level of physical fitness class XI student of SMAN 4 Sidoarjo. This type of research is non-experimental research through quantitative approach with a correlational design. The population in this study were all students of class XI SMA Negeri 4 Sidoarjo. The amount of population are 324 students. While the sampling technique used was cluster sampling with a sample size of 29 students. Instrument in this study is the IMT / U for nutrient status, sport habits questionnaire, and MFT tests to measure physical fitness. Data analysis used logistic regression. Based on the analysis of the data found that the nutrient status had sig value 0.007 <ρvalue (sig) 0.05, with a coefficient of determination of 43%, then Ho1 is rejected and Ha1 accepted. So, there is a relationship between nutrient status with physical fitness by 43%. While sport habits have sig 0.922> ρvalue (sig) 0.05, Ho2 accepted and rejected Ha2. So, there is no relationship between sport habits with physical fitness. Logistic regression results show the results sig. 0.215. This suggests that sig (0.397)> alpha 0.05, which means that H0 is accepted and H1 is rejected. Thus, there was no correlation between nutrient status and sport habits with the level of physical fitness.   It can be concluded that there is no significant corelation between nutrient status and sport habits with physical fitness levels in class XI SMA Negeri 4 Sidoarjo. Keywords: Nutrient Status, Sport Habits, Physical Fitness.